The impact of reputation and identity congruence on employer brand attractiveness. Issue 2 (7th April 2015) - Xie, Chunyan; Bagozzi, Richard P.; Meland, Kjersti V.
Abstract : Purpose: – The purpose of this paper is to extend research on employer branding in the recruitment context. The authors develop a model that integrates research from employer branding, social identity theory, and person-organization fit in order to investigate the impact of company reputation and identity congruency between organizations and their job applicants on the attractiveness of an employer brand. Design/methodology/approach: – An online survey was conducted to test the theoretical model in a recruitment context in the Norwegian offshore industry. Structural equation modelling is employed in the data analysis. Findings: – A key finding is that a company's reputation and identity congruence between applicants' self-identities and their perceived organization identity affect job applicants' job pursuit intentions through mediation of cognitive social identity. Moreover, identity congruence predicts applicants' cognitive identification with the company. Practical implications: – The study suggests that managers should try to map and understand central characteristics that describe job applicants' identities and strive to provide applicants with access to necessary information about the company to form cognitive identification with the company. Originality/value: – The authors extend research on employer branding by incorporating social identity and attitude as mediators between symbolic and instrumental attributes of an employer brand and its attractiveness. This study also deepens research on social identity by including explicitly a comparison process between applicants' self-identities and their perceived organizational identity, which leads to applicants' identification with the company.